Unraveling the laser decal transfer-based printing of ZnO ceramic towards FEP-ZnO-based Piezo-Tribo hybrid nanogenerators - Arpit Kumar Singh; Anshu Sahu; Palani Iyamperumal Anand (Nano Trends)
In this growing technological world, laser decal transfer has emerged as a groundbreaking technique due to its ability to offer high precision, material versatility, and design freedom. While various combinations of metals have been explored for applications ranging from aerospace and biomedical devices to micro-electromechanical systems (MEMS), it works on conventional printing processes that rely on wire or powder as raw materials, which limit their applicability in certain end-use cases. In contrast, laser decal transfer enables the precise deposition of materials without phase changes, making it particularly suitable for advanced applications where chemical and functional integrity must be maintained. Most MEMS devices are fabricated using either lithography-based processes or microfabrication systems, both of which involve phase change during fabrication. This phase change often alters the chemical and functional properties of the devices, highlighting the need for a fabrication method that preserves the original material characteristics. With advancements in technologies, a thin film-based laser decal transfer setup is yet to be fully explored for printing thin-film materials in pixelated form over substrates, enabling substrate- and material-independent processes.The present work focuses on the development of a laser decal transfer-based printing process using thin film as feed material for the fabrication of MEMS devices for piezo-tribo hybrid applications. Surface modification is explored to enhance static charge retention over surfaces. Initially, a silicon wafer is coated with a sacrificial layer over which a piezo-ceramic (ZnO) is sputtered to develop a seed layer. A CO2 laser (λ=10.6 μm) is utilized in the proposed work, with a detailed investigation of laser processing parameters conducted for effective control over piezo-ceramic transfer and selective positioning. The influence of laser fluence and standoff distance is analyzed, and laser pulse overlap's effect on heat-affected zones and material transfer is thoroughly examined.Based on optimized parameters, the selective control and transfer of ceramic onto solid and flexible substrates are demonstrated. The selectively transferred nanoparticles in various patterns are further grown using a hydrothermal technique. Material characterization is performed to confirm the pixelated transfer of ceramic without phase transfer, and the surface adhesivity of transferred material is analyzed using a scotch tape test. Finally, a ZnO-FEP-based piezo-tribo hybrid device is fabricated, tested for both piezoelectric and triboelectric responses, and further explored for hybrid device applications. The proposed technology of laser decal transfer has significant potential for the complex printing of sensors without directly affecting the material, allowing for controlled gradient-based properties. This approach holds great promise for futuristic technologies enabling the selective printing of functional piezoelectric and triboelectric sensors.